2019
DOI: 10.1177/0165551519860464
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-sharing and collaborative behaviour: An empirical study on a Portuguese higher education institution

Abstract: Collaboration has been considered a way to address the challenges of the 21st century, fostering the necessary innovation, growth and productivity for all parties involved. Several studies reveal that collaboration can be strongly influenced by knowledge sharing. The literature suggests that this topic is quite relevant and that there is an evident lack of empirical studies that properly investigate the relationship between knowledge-sharing and collaborative behaviour in Higher Education Institutions (HEIs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
6
22
1
Order By: Relevance
“…The results of this study show that tacit knowledge sharing has a positive impact on innovation performance in the construction supply chain, and the view is supported by many previous literatures (Chedid et al , 2020; Choi et al , 2019). However, it is also found that explicit knowledge sharing has no significant correlation with innovation performance.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study show that tacit knowledge sharing has a positive impact on innovation performance in the construction supply chain, and the view is supported by many previous literatures (Chedid et al , 2020; Choi et al , 2019). However, it is also found that explicit knowledge sharing has no significant correlation with innovation performance.…”
Section: Discussionsupporting
confidence: 87%
“…Their results showed that faculty members' perceptions of the importance of sharing teaching and research materials was the most influential factor for knowledge sharing among faculty, but trust was not a statistically significant factor. Another study at a Portuguese university found trust to strongly influence faculty members' intention to share knowledge (Chedid et al, 2020). Yet another study applied game theory to examine knowledge sharing between faculty in Iran (Tabatabaei et al, 2019).…”
Section: Framework For Knowledge Sharingmentioning
confidence: 99%
“…First, scholars have identified that knowledge sharing is significant in promoting IWB (Andreeva et al, 2017). The related argument is that for employees to be able to engage in innovative behaviours, they require continuous forms of diversified knowledge to facilitate task performance and increase their confidence level (Chedid et al, 2019;Radaelli et al, 2014). Second, employees' levels of commitment at work are correlated with their performance and willingness to engage in positive behaviours.…”
Section: Introductionmentioning
confidence: 99%